BIOMASU ENERĢIJA LAUKU VIDĒ (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
The global trend in population growth let us forecast that population will increase to 8500 millions by the year 2025. The main task for future development is sustainable food production for growing population. At the same time fossil fuel resources will decrease and we shall turn to renewable energy resources. The goal to double amount of renewable energy consumption have been advanced in White Paper of European Union - " Energy for the future: Renewable sources of energy" (1997). The more significant part (74%) of renewable energy sources has been planned for Biomass energy. Latvia on its way to European Union have the same tasks of Bioenergy development as in White Paper of European Commission:" Biomass energy technologies have preference in rural areas for different reasons:Biomass is the main product in everyday agricultural production.Increasing productivity of food production create the land reserves for biomass, as energy source, production.Rural community has better understanding of environment protection problems and necessity to prevent Global Climate Change.Biomass technologies can create alternative jobs within and outside agriculture that is crucial to the health and sustainability of rural economy development.In the rural area open water systems (rivers and lakes) and wetlands also play an important role in the functioning of the agricultural ecosystem. For ages lake ecosystems have been acting as sinks for collecting organic and minerogenic matter (Bjork, 1988). At the same time soil cultivation in the catchment area of natural open water systems interacts with water flows. It has been stated that the intense land cultivation over the last 100 years has led to irreversible charge flows (matter loss, mainly alkaline metal cations) from agricultural soils by surface water flows. Matter losses from agricultural areas may amount to more than one ton per hectare a year (Ripl et al., 1994). Soil restitution by transport of matter opposite to water flow (sludge, sediments, and compost) is recommended.Leading to soil impoverishment and erosion, the organic residue removal from the fields must be limited. The biomass quantity whose removal has no significant impact on the carbon cycle varies from 20 to 50 %. Yearly production amount of cereal straw in Latvia in 1997 was 850907 tons If 20% from total amount could be used for energy production -171 0001 straw it is equal to heat capacity o f57 000 t of oil. More preferable are biomass usage technologies with minimal transport expenses:Development of mechanisation for technologies of straw and another plant material briquetting and pelleting..Constructed Reedbeds for Effluent Treatment is simplest and cheapest system for disposing of domestic sewage for rural situations. At the same time Reedbeds are the source of Biomass 20 -251per ha of dry matter annually.Composting heat plants' technologies. The heating energy, obtained in the biomass aerated composting process with temperature up to 50 X! can be used for different purposes where the low temperature heat is accepted.